2011
DOI: 10.1016/j.bbamem.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Membrane bilayer properties of sphingomyelins with amide-linked 2- or 3-hydroxylated fatty acids

Abstract: The bilayer properties and interactions with cholesterol of N-acyl hydroxylated sphingomyelins (SM) were examined, and results were compared to nonhydroxylated chain-matched SM. The natural OH(D)-enantiomer of hydroxylated SM (with 16:0 or 22:0 acyl chain lengths) analogs was synthesized. Measuring steady-state diphenylhexatriene anisotropy, we observed that pure 2OH-SM bilayers always showed higher (5-10 °C) gel-liquid transition temperatures (T(m)) compared to their nonhydroxylated chain-matched analogs. Bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This report is in line with our observation that the OH group does not significantly alter the partitioning of the Gb 3 species in phase-separated GUVs.H owever,i nap revious study,wefound that the 2-OH group influences the fraction of l o phase in phase-separated supported lipid bilayers. [21] In the case of the hydroxylated C 24:0 fatty acid, the l o fraction was smaller than that of the nonhydroxylated species.S lotte and co-workers [47] showed that the 2-OH group increases the hydration in the membrane interface and decreases the affinity of as phingolipid for sterols.T he same was found by Lingwood et al [48] and Yahi et al [49] and implies that the The partition of the Gb 3 species harboring asaturated fatty acid (C 24:0 ) were compared with that with an attached unsaturated fatty acid (C 24:1 ). The mean values are given as ared star,w hile the red lines show the median value (Table 1).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This report is in line with our observation that the OH group does not significantly alter the partitioning of the Gb 3 species in phase-separated GUVs.H owever,i nap revious study,wefound that the 2-OH group influences the fraction of l o phase in phase-separated supported lipid bilayers. [21] In the case of the hydroxylated C 24:0 fatty acid, the l o fraction was smaller than that of the nonhydroxylated species.S lotte and co-workers [47] showed that the 2-OH group increases the hydration in the membrane interface and decreases the affinity of as phingolipid for sterols.T he same was found by Lingwood et al [48] and Yahi et al [49] and implies that the The partition of the Gb 3 species harboring asaturated fatty acid (C 24:0 ) were compared with that with an attached unsaturated fatty acid (C 24:1 ). The mean values are given as ared star,w hile the red lines show the median value (Table 1).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Individual colonies were isolated using cloning cylinders Scheme. 1 and 2-OH FAMEs were prepared by methylation prior to separation on a silica plate. The isolated 2-OH FAMEs were then derivatized with ( R )-MTPA-Cl and analyzed by GC-NCI-MS. As shown in Fig.…”
Section: Generation Of Chinese Hamster Ovary Cell Line Stably Over-exmentioning
confidence: 99%
“…FA hydroxylation alters the packing structures of membrane microdomains and thus could regulate cellular functions of membrane-associated proteins ( 1 ). FA 2-hydroxylase (Sigma) and transferred to 24-well plates in duplicate.…”
mentioning
confidence: 99%
“…In the case of the hydroxylated C 24:0 fatty acid, the l o fraction was smaller than that of the nonhydroxylated species. Slotte and co‐workers showed that the 2‐OH group increases the hydration in the membrane interface and decreases the affinity of a sphingolipid for sterols. The same was found by Lingwood et al .…”
Section: Resultsmentioning
confidence: 90%